Analysis of the Improvement of Work Ability, Job Satisfaction, and Compensation and Its Impact on the Performance of Employees at PTPN IV Regional 1 Rantauprapat Plantation - Lindawati Ginting; Raja Saul Marto Hendry; Usmala Dewi Siregar (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effect of work ability improvement, job satisfaction, and compensation on employee performance at PTPN IV Regional 1 Kebun Rantauprapat. The background of this research is based on the importance of effective human resource management in enhancing productivity and achieving corporate performance targets within the plantation sector. Optimal work ability, high levels of job satisfaction, and a fair and competitive compensation system are considered key determinants in improving employee performance. This research employs a quantitative approach using a survey method. The population consists of all employees at PTPN IV Regional 1 Kebun Rantauprapat, with a saturated sampling (census) technique applied. Data were collected through questionnaires and analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results indicate that work ability improvement, job satisfaction, and compensation partially have a positive and significant effect on employee performance. Simultaneously, these three independent variables also significantly influence employee performance. These findings suggest that the company should optimize training and competency development programs, enhance performance-based compensation systems, and create a supportive work environment to sustainably improve employee satisfaction and performance.